HPIP: a predictor of lymph node metastasis and poor survival in cervical cancer - Cao, Shan (Onco Targets Ther, 2017)
BACKGROUND: The aim of this study was to explore the relationships of HPIP expression status with the clinicopathological variables and survival outcomes of patients with cervical cancer (CC). METHODS: We compared the HPIP expression of 119 samples from CC tissues, 20 from cervical intraepithelial tissues, and 20 from normal cervical tissues by using immunohistochemical staining. RESULTS: It was observed that the ratio of elevated HPIP expression was higher in CC tissues than in cervical intraepithelial neoplasia (P=0.017) and normal cervical tissues (P=0.001). In addition, there was an association between HPIP and clinicopathological factors, such as histological grade (P<0.001), stromal infiltration (P=0.015), lymph node metastasis (P<0.001), lymphovascular space invasion (LVSI; P=0.026), and recurrence (P=0.029). Furthermore, multivariate Cox regression analysis revealed that high HPIP expression (P=0.027 and P=0.042) as well as the International Federation of Gynaecology and Obstetrics stage (P=0.003 and P=0.009), lymph node metastasis (P=0.031 and P=0.017), and LVSI (P=0.024 and P=0.046) were independent prognostic factors. In addition, we demonstrated that high HPIP expression (P=0.003) and LVSI (P<0.001) were independently related to lymph node metastasis. CONCLUSION: Elevated HPIP expression may contribute to the progression and metastasis of CC and may also serve as a new biomarker to predict the prognosis of CC.